Analisa Pengaruh SOP ( Standard Operating Procedure ) Terhadap Kinerja Waiter Dan Waitress Di In Bloom Restoran Hotel Ayaartta Malioboro Yogyakarta, Indonesia - Slamet Supriyanto; Lutfi Hendriyati (Journal of Tourism and Economic, 2021)
Standard operating procedures or commonly called SOPs are important things that every company must have and must be a guide in carrying out work activities by all waiters and waiters at In Bloom Restaurant Hotel Ayaartta Malioboro Yogyakarta. This research uses a quantitative approach method, using data from questionnaires and uncovering problems in the form of numerical scores, which are then processed and tested by statistical analysis techniques in an effort to reveal the performance and effectiveness of SOP implementation in carrying out tasks at Bloom's Restaurant.